The supervisory relationship as a predictor of mental health outcomes in doctoral students in the United Kingdom - Mavrogalou-Foti, Alkistis P.; Kambouri, Maria A.; Çili, Soljana (Frontiers in Psychology, 2024)
Introduction The process of a doctorate degree has been implicated in the onset and exacerbation of mental health problems among doctoral students. Previous studies have suggested that the student-supervisor relationship may predict emotional wellbeing and mental health outcomes in doctoral students in the UK. However, these studies were conducted before the COVID-19 pandemic and often used unstandardized measures to investigate supervisory styles. Methods The present study was part of the Better Together project, a wellbeing initiative for doctoral students in the UK. It explored the predictive ability of aspects of the student-supervisor relationship with regards to doctoral students’ mental health outcomes. The sample consisted of 141 students doing a research-based doctorate degree in the UK. The survey included demographic questions and questionnaires assessing supervisory styles, the discrepancy between actual and preferred supervisory relationship, depression, anxiety, and stress. Results A large proportion of participants fell in the severe and extremely severe categories in the depression, anxiety, and stress sub-scales. Multiple regression analyses indicated that both supervisory styles and discrepancy significantly predicted students’ mental health outcomes. More specifically, higher scores in the uncertain supervisory style, which is characterized by indecisiveness and ambiguity, were linked with higher scores in depression, anxiety, and stress. Discussion The findings provided new insights concerning the aspects of the student-supervisor relationship that are related to the mental health issues of doctoral students in the UK. They have important implications for future research and supervision practice.